Dispute resolution mechanism by dispute resolution board according to FIDIC contract model and experience for Vietnam - Lam, Le Doan; Tho, Le Pham Anh (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The article “Dispute resolution mechanism by the Dispute Board according to the FIDIC contract form and experience for Vietnam” researches the theoretical issues related to the FIDIC Contract and the Dispute Settlement Board of the FIDIC. In addition, the article also focuses on researching and analyzing the practice of applying dispute settlement mechanisms by Dispute Settlement Boards in various nations throughout the world. The article's usefulness stems from the knowledge gained while researching this dispute resolution mechanism in countries throughout the world, as well as the present situation of Vietnamese law, which provides solutions and recommendations based on Vietnamese law.